Forensic Digital Analysis for CCTV Video Recording - Sukamto, Pria; Ispandi; Arman Syah Putra; Nurul Aisyah; Rohmat Toufiq (International Journal of Science, Technology & Management, 2022)
The background of this research is how to make a video that can be analyzed as forensic data to prove the truth of the video, therefore with forensics it can be used as evidence if the video contains incorrect data or contains data capable of crime so that it can be used as data forensics. The method used in this study is to use the literature review method which uses the basis of many previous studies. From journals and books based on similar research, so that it can help develop existing problems to the latest problems so that they can find novelty in this research. The problem raised in this research is how to make a video from a CCTV that can be proven, by certain methods in order to make the video as forensic data, that can be proven so that it can be developed into data containing crimes that can be used as evidence. The purpose of this study is how to find the right method in order to analyze a CCTV video, so that it can be used as evidence on forensic data with the NIST method, it can be proven that this method is the right method in analyzing a video, so that it can be used as evidence and as data forensics.